Crumb rubber as partial replacement for fine aggregate in concrete: An overview. (8th August 2022) - Ren, Fengming; Mo, Jinxu; Wang, Qing; Ho, Johnny Ching Ming
Highlights: Waste rubber tyres can be effectively consumed as partial replacement for fine aggregate in concrete. Surface modification improves mechanical performance of rubber/paste interfaces. Strength prediction models of crumb rubber concrete are proposed based on experimental data. Impact resistance of concrete is greatly improved in the presence of crumb rubber. Durability properties of crumb rubber concrete are comprehensively summarized. Abstract: Waste tyres cause tremendous pressure and ecological issues for the entire tyre industry when accumulated in cultivated land or combusted. Crumb rubber (<5 mm) grinded from waste tyres was introduced to substitute for natural fine aggregate in concrete and effectively solves the consumption challenge. This paper reviews the performance of concrete with crumb rubber as fine aggregate, providing evidence for crumb rubber concrete (CRC) materials design and application. Crumb rubber is characterized with light specific gravity, hydrophobicity and air entrapment in comparison with natural fine aggregate, inducing significant reduction in workability of fresh CRC and exhibiting poor bonding performance with cementitious matrix. By summarizing the compressive/tensile strength, elastic modulus and fracture behavior of CRC at various rubber content, prediction models of strength reduction factors are proposed. The main reasons for strength deterioration are weak interface transition zone (ITZ) performance and non-uniform distribution of rubber particles. Water/chloride permeability, electrical/carbonation resistance and drying shrinkage of CRC are discussed for durability performance of CRC. Physical/chemical pre-treatments of rubber could alleviate the hydrophobicity and improve the mechanical and durability performance of transition zones between rubber and cement paste. Accordingly, scopes concerning the recycling of crumb rubber and its performance optimization are expected in future studies.